Sex differences in 1‐year mortality risks in older patients experiencing a first acute heart failure hospitalization. Issue 3 (12th December 2018) - Formiga, Francesc; Moreno‐Gonzalez, Rafael; Chivite, David; Yun, Sergi; Franco, Jonathan; Ariza‐Solé, Albert; Corbella, Xavier
Abstract : Aim: To assess whether 1‐year mortality in older patients experiencing a first admission for acute heart failure was related to sex, and to explore differential characteristics according to sex. Methods: We reviewed the medical records of 1132 patients aged >70 years of age admitted within a 3‐year period because of a first episode of acute heart failure. We analyzed sex differences. Mortality was assessed using multivariate Cox analysis. Results: There were 648 (57.2%) women (mean age 82.1 years) and 484 men (mean age 80.1 years). There were some differences in risk factors: women more often had hypertension, and less frequently had coronary heart disease and comorbidities (women more often had dementia, and men more often had chronic obstructive pulmonary disease, chronic kidney disease and stroke). Women were treated more frequently with spironolactone. The 1‐year all‐cause mortality rate was 30.2% (30.7% women and 29.5% men). Multivariate Cox analysis identified an association between reduced heart failure (hazard ratio [HR] 0.35, 95% confidence interval [95% CI] 0.21–0.59), hemoglobin <10 g/dL (HR 1.99, 95% CI 1.16–3.40), systolic blood pressure (HR 0.98, 95% CI 0.97–0.99), previous diagnosis of dementia (HR 2.07, 95% CI 1.12–3.85), number of chronic therapies (HR 1.12, 95% CI 1.05–1.19) and 1‐year mortality in women. In men, an association with mortality was found for low systolic blood pressure (HR 0.97, 95% CI 0.97–0.98) and higher potassium values (HR 1.42, 95% CI 1.01–2.00). Conclusions: Among older patients hospitalized for the first acute heart failure episode, there is a slightly higher predominance of women. There are sex differences in risk factors and comorbidities. Although the mortality rate is similar, the factors associated with it according to sex are different.Geriatr Gerontol Int 2019; 19: 184–188 .